Improving Children's Cognitive Abilities About Name Days In English Through Singing Method - Nelli Amanda Sari; Nadila Adha Lubis; Yufa Ainun Hidayat; Aprina Harahap; Bani Amirul (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
Early childhood cognitive development is an important aspect in the learning and growth process. One effective method to improve children's cognitive abilities is to use the singing method. This method utilizes music and song lyrics to help children learn in a fun and easy to remember way. This study aims to evaluate the effectiveness of the singing method in improving the cognitive abilities of young children, especially in terms of mastering the names of days in English. The research results showed that the singing method was proven to be an effective approach to improve understanding and retention of information related to the names of the days.